Analysis Of Maintenance Procedures For Archives Facilities And Infrastructure Division Of Human And General Resources Of The National Library Of The Republic Of Indonesia - Ayu Suwarni, Shofa; Wiradendi Wolor , Christian; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research uses a qualitative descriptive approach, namely by describing and examining the problems found. This research data was obtained through observation, interviews and documentation, and previous research articles. The aim of this research is to find out about the procedures for maintaining archival facilities and infrastructure in the human and general resources division of the library. National Republic of Indonesia which includes the availability of good facilities and infrastructure for archival activities as well as obstacles and solutions in maintaining archival facilities and infrastructure. From the results of this research it can be seen that the procedures for maintaining facilities and infrastructure in archival storage in the human resources and general divisions which is still inadequate. This can be seen from the capacity of the filling cabinet being used which is full, resulting in a lot of archives piling up in boxes that are not immediately organized and the archive storage space being poorly maintained. The solution that must be implemented is to carry out routine maintenance on the archives room, and involve related parties in the process of implementing this solution so that all parties have responsibility for maintaining archival facilities and infrastructure.